Vaccination of nulliparous gilts against porcine epidemic diarrhoea can result in low neutralising antibody titres and high litter mortality - Galindo-Castañeda, Lourdes M.; Chacón-Salinas, Rommel; Quintero, Víctor; Sanchez-Betancourt, José I.; Cobos-Marín, Laura (Austral Journal of Veterinary Sciences, 2021)
Porcine epidemic diarrhoea (PED) is a disease caused by an alphacoronavirus and the symptoms include watery diarrhoea and vomiting, with more than 80% mortality amongst newborn piglets. The placentation in sows hinders the transference of antibodies to the foetus, therefore, the vaccination of pregnant females and transference of antibodies to piglets through colostrum are essential to protect them against virus particles. The aim of the study was to determine whether vaccination of nulliparous gilts could induce a high colostrum antibody titre and lower litter mortality, in comparison with vaccinated multiparous sows previously exposed to the virus. Samples of colostrum were obtained from 11 nulliparous gilts with two previous vaccinations (inactivated vaccine) and from 9 multiparous sows with three or more vaccinations (inactivated vaccine) that had been exposed to the virus. The IgG antibody titre was determined through anti-PED enzyme-linked immunosorbent assays (ELISA) and the neutralisation of antibodies was evaluated through plaque reduction neutralisation tests (PRNT). The colostrum of nulliparous gilts, when compared to the multiparous sows, presented a lower anti-PED IgG antibody titre as well as fewer neutralising antibodies. Furthermore, the piglets of multiparous sows experienced higher survival in comparison with those of nulliparous gilts (P<0.01), and mortality was dependent on the ’farrowing’ variable (P<0.01). In conclusion, these results show that vaccinating nulliparous gilts does not increase the survival of their piglets in comparison with multiparous sows and that the IgG titres and neutralising antibodies are significantly lower in the former. These results suggest that a modified vaccine strategy is needed for nulliparous gilts to increase piglet protection.